2021
DOI: 10.1155/2021/2305695
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Parameters of a Formulation Containing Cinnamaldehyde for Use in Treatment of Oral Fungal Infections: An In Vivo Study

Abstract: Objective. We aimed to define the safety and toxicity of both isolated and embedded cinnamaldehyde using a pharmaceutical formulation for the treatment of oral fungal infections in an in vivo study. Materials and Methods. Acute toxicity was assessed in studies with Galleria mellonella larvae and Danio rerio embryos (zebrafish), and genotoxicity was assessed in a mouse model. The pharmaceutical formulation (orabase ointment) containing cinnamaldehyde was evaluated for verification of both in vitro antifungal ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, the antibacterial and antiviral activity of cinnamaldehyde and terpinen-4-ol have also been well documented in the research articles 43,44 . Cinnamaldehyde was found to be not toxic to vertebrates or invertebrates in an in vivo trial conducted by Alves et al 45 . Subash Babu et al 46 found that oral administration of cinnamaldehyde in induced diabetic rats produces a significant antihyperglycemic effect and simultaneously help to reduce total cholesterol and triglyceride levels effect.…”
Section: Health Benefits And/or Potential Clinical Application Of Ess...mentioning
confidence: 99%
“…Furthermore, the antibacterial and antiviral activity of cinnamaldehyde and terpinen-4-ol have also been well documented in the research articles 43,44 . Cinnamaldehyde was found to be not toxic to vertebrates or invertebrates in an in vivo trial conducted by Alves et al 45 . Subash Babu et al 46 found that oral administration of cinnamaldehyde in induced diabetic rats produces a significant antihyperglycemic effect and simultaneously help to reduce total cholesterol and triglyceride levels effect.…”
Section: Health Benefits And/or Potential Clinical Application Of Ess...mentioning
confidence: 99%
“…Many studies based on the classification of teratogenic and non-teratogenic substances have demonstrated a high correlation of toxic response between fish and mammals, of over 72%. Therefore, fish embryo and larvae are considered one of the relevant, reliable, controllable and reproducible models for studying the impact that various chemical substances have on the human body (Genest, 2019;Alves et al, 2021). Recently, numerous toxicology studies on fish embryos and larvae have been published, including studies testing the effects of food additives.…”
Section: Introductionmentioning
confidence: 99%